Photocatalytic Cycloadditions Enabled by a Lithium Perchlorate/Nitromethane Electrolyte Solution. Issue 47 (19th November 2018) - Nagahara, Shingo; Wakamatsu, Hiroki; Okada, Yohei; Chiba, Kazuhiro
Abstract : Photocatalytic cycloadditions involving carbon–carbon bond formation in the absence of an external sensitizer are described. The use of a lithium perchlorate/nitromethane electrolyte solution exhibiting remarkable Lewis acidity is the key for the successful transformations. According to the UV/Vis measurements, an electron donor–acceptor complex did not form and nitromethane was expected to function as the initial sensitizer for the reactions. Although the mechanisms are still under debate, both electron‐ and energy‐transfer processes could be involved, both of which are triggered by excited nitromethane in combination with molecular oxygen. Abstract : Photocatalytic cycloadditions involving carbon–carbon bond formation in the absence of an external sensitizer are described. The use of a lithium perchlorate/nitromethane electrolyte solution exhibiting remarkable Lewis acidity is the key for the successful transformations.